Analysis and design of mechanically spliced precast bridge columns. (1st April 2023) - Tazarv, Mostafa; LaVoy, Mathew; Sjurseth, Theodore; Greeneway, Evan; Wehbe, Nadim
Highlights: Seismic capacities and demands of mechanically spliced bridge columns are investigated through 950 analyses. Couplers may reduce the column displacement ductility capacity by 45 %. Couplers may alter the column displacement demands by 10 %. Current design methods for mechanically spliced bridge columns are evaluated. Abstract: Reinforcement continuity in concrete members is traditionally achieved through lap splicing. An alternative is to use couplers to mechanically connect bars. Mechanical bar splices have been used in conventional and accelerated bridge construction (ABC) applications usually in capacity-protected and/or non-seismic members. Nevertheless, couplers are not currently allowed in the US national design codes to be used in the plastic hinge region of bridge columns in high seismic regions mostly due to uncertainty on their structural effects. This ban has also prevented the use of couplers as an ABC bent connection. A comprehensive analytical study was carried out to determine the effects of bar couplers on the RC bridge column seismic performance, specifically displacement capacities and demands. Modeling methods were proposed and validated against multiple test data. Subsequently, more than 950 pushover and nonlinear dynamic analyses were carried out on mechanically spliced circular and square bridge columns using the validated models. The results from the pushover analyses showed that couplers can reduce the columns displacement ductility capacity up to 45 %. A trend between the coupler length, rigidity, and the column displacement ductility capacity was established. Furthermore, the effect of couplers on the column displacement demands was found to be less than 10 % compared with unspliced columns. Finally, available design methods for mechanically spliced RC bridge columns were evaluated using test data for eight large-scale bridge columns.